PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN KELAS III SEKOLAH DASAR - Sari, Refiana; Nurwahidin, Muhammad; Hariyanto; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat. This study aims to determine the effect of the application of the wordwall-assisted discovery learning model on the learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat. The method used in this study is a quasi-experimental design with a non-equivalent control group design. This study uses a saturated sample technique with a sample size of 15 students and a population of 31 students. Data collection techniques use test techniques in the form of multiple-choice questions and non-test techniques in the form of observation sheets. Hypothesis testing uses a simple linear regression formula. The results of the study indicate that there is an effect of the application of the Wordwall-assisted Discovery Learning model on the learning outcomes of Pancasila and Citizenship Education in grade III of SD Negeri 4 Metro Barat.